Zoophilia in an adolescent with high-functioning autism from Sri Lanka. (October 2017) - Chandradasa, Miyuru; Champika, Layani
Objective: Zoophilia is a rare paraphilic disorder with intense sexual urges involving animals. Autism is characterised by impairments in social communication and repetitive, restricted behaviours (RRB). Reported cases of zoophilia are limited worldwide, and zoophilia in autism is rarer. Method: This is a case report describing this unique and relatively unrecognised association in a male adolescent from Sri Lanka. Results: A 17-year-old boy diagnosed with autism has average intelligence and academic capabilities. He had spent increasing time at his grandparents' cattle house. First, he was found masturbating near the cows and later having penetrative intercourse with a heifer. The shocked parents first sought traditional healing in the form of 'thovil', a demonic ritual of exorcist nature. Later, clinical evaluation found intense sexual urges towards cattle, which had led to marked distress and academic impairment. Sex hormone profile was normal. The adolescent was treated with a combination of cognitive–behaviour therapy and a selective serotonin reuptake inhibitor. Conclusion: We postulate that his persistent social difficulties contributed to the development of a paraphilic disorder. Unlike with his RRBs, he was markedly distressed about this sexual behaviour. Further research is required to explore this rarely reported, potential association.